1999
DOI: 10.1002/1529-0131(199909)42:9<1854::aid-anr9>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Long-term course and outcome of functional capacity in rheumatoid arthritis: The effect of disease activity and radiologic damage over time

Abstract: Functional capacity is strongly influenced by disease activity throughout the course of RA. Even in longstanding RA, disease activity proves to be the main determinant of the HAQ score for functional capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
209
7
10

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(247 citation statements)
references
References 29 publications
21
209
7
10
Order By: Relevance
“…RANKL acts as a potent osteoclast activator producing bone erosions in adjuvant arthritis (2). The limited predictive power of RANKL in our study may show that osteoprotegerin, its endogenous inhibitor, modifies RANKL-induced joint damage, in addition to the interaction with IFN␥ above.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…RANKL acts as a potent osteoclast activator producing bone erosions in adjuvant arthritis (2). The limited predictive power of RANKL in our study may show that osteoprotegerin, its endogenous inhibitor, modifies RANKL-induced joint damage, in addition to the interaction with IFN␥ above.…”
mentioning
confidence: 74%
“…Rheumatoid arthritis (RA) is characterized by progressive irreversible joint damage resulting in increasing disability (1,2). However, joint damage accumulation is highly variable, differing up to 10-fold between individuals after 8-12 years of disease (3,4).…”
mentioning
confidence: 99%
“…This process can be measured by quantifying the changes in joint space narrowing and erosions that are visible on serial plain radiographs (2). Radiographic joint damage is associated with long-term functional disability (3) and is the accepted assessment tool for monitoring clinical progression and long-term response to therapy (4). Radiographic progression develops over many months and years, however, and is not suitable for assessment of treatment efficacy over short periods.…”
mentioning
confidence: 99%
“…Our bare model had the weakest fit, and adding variables of disease characteristics (medications, ESR, Patient Activity Scale, and DAS28) substantially improved model fit in the administrative and clinic models. Previous studies have shown disease characteristics, rather than comorbidity, to be more closely related to outcomes (28,35). This explains why the comorbidity indices had maximal improvement in model fit in the bare model and progressively less improvement in the administrative and clinic models.…”
Section: Discussionmentioning
confidence: 92%